QUANTUM MECHANICAL DESCRIPTORS OF NILOTINIB’S IMPURITIES - Mitra, Debanjan (Innovare Journal of Sciences, 2018)
Objective: Mutagenic/genotoxic impurities in the clinically approved drugs have been a major concern for the pharmaceutical industry. Nilotinib (N), which is an approved drug of chronic leukemia, has a number of impurities (nilotinib impurity [NI]-3, NI-5, and NI-12). For drugs, either semi-empirical or quantum mechanical (QM) or topological molecular descriptors (MDs) have been popular for QSAR studies. However, details of MDs for impurities are yet to be established. Thus, the objective of the study has been to compute QM-based MDs for impurities of N and to compare them with that of approved drugs to identify MDs of the former in relation to their known genotoxic/mutagenic properties. Methods: Impurities are optimized by B3LYP/6-311G (d,p) level of theory and ionization potential (IP), electron affinity (EA), and other MDs are determined. Further, non-linear optical (NLO) descriptors such as dipole moment (DM) and polarizability (Î±) are also determined. Results: Impurities of N show much deviation of IP, EA, MD, Î±, and other properties from the reported mean values of approved drugs. Unlike NI-5 and NI-12, NI-3 shows increase in DM ( double) and Î± properties, which may point to its higher interactivity with cellular targets (like DNA/ RNA/protein), might be due to additional substituents, Ï€-conjugation, and planarity in its structure. The latter seems to be due to compensation of oppositely sensed dihedral properties of the structure of NI-3. Conclusion: The study identifies QM-based differential MDs for impurities of N, which seems to have a relationship with their genotoxicity/ mutagenicity properties. Similar studies can be done for other such systems. Â